Altitude and risk of depression and anxiety: findings from the intern health study. (17th November 2019) - Kious, Brent M.; Bakian, Amanda; Zhao, Joan; Mickey, Brian; Guille, Constance; Renshaw, Perry; Sen, Srijan
Abstract: Multiple studies suggest that the risks of depression and suicide increase with increasing altitude of residence, but no studies have assessed whether changing altitude changes these risks. To address this gap, this study used data from the Intern Health Study, which follows students from the end of medical school through the first year of residency, recording depression via the 9-item Patient Health Questionnaire (PHQ-9), anxiety via the 7-item Generalized Anxiety Disorder Questionnaire (GAD-7), and multiple risk factors for these symptoms. Data from 3764 medical students representing 46 schools and 282 residencies were available. Odds ratios (OR) representing the effects of altitude on psychiatric symptoms were estimated using generalized linear models. After excluding participants with missing altitude data, 3731 medical students were analyzed. High altitude residence (> 900 m) was significantly associated with PHQ-9 total score (OR = 1.32, 95% CI = 1.001–1.75, p < 0.05), and PHQ-9 suicidal ideation (OR = 1.79, 95% CI = 1.08–0.02, p = 0.02). Moving from low to high altitude was significantly associated with PHQ-9 total score (OR = 1.47, 95% CI = 1.087–1.98, p = 0.01), GAD-7 total score (OR = 1.40, 95% CI = 1.0040–1.95, p < 0.05), and PHQ-9 suicidal ideation (OR = 1.10, 95% CI = 1.01–1.19, p = 0.02). The data suggest that moving from low to high altitude is associated with increasing symptoms of depression, anxiety, and suicidal ideation.